2022
DOI: 10.20473/juxta.v13i22022.67-72
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Medication, Surgery, and Combination Therapy to Decrease Intraocular Pressure on Glaucoma Outpatient at Outpatient Ophthalmic Clinic Dr. Soetomo General Hospital Surabaya in January – December 2017

Abstract: Highlights:1. Combination of medication and surgery on glaucoma had the least post-therapy intraocular pressure.2. There was no significant difference in the efficacy of drugs, surgeries, and combination of both therapies for glaucoma intraocular pressure reduction. AbstractIntroduction: Glaucoma leads to blindness in its end stage. Quality of life drops as visual field loss as progressive optic nerve damage since high intraocular pressure elevation. Glaucoma treatment focused on aqueous humor regulation, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another study reported that glaucoma was most commonly found in people aged 50-64 years (Yolanda et al 2021, Praba et al 2021. Unfortunately, treatment of latestage glaucoma through medication, surgery, and combination therapies did not result in significant improvement (Pratista et al 2022). In Nigeria, the National Blindness and Visual Impairment Survey conducted in 2005-2007 reported that 4.2% of people aged >40 years were blind and 11.5% had moderate to severe visual impairment (Gascoyne et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that glaucoma was most commonly found in people aged 50-64 years (Yolanda et al 2021, Praba et al 2021. Unfortunately, treatment of latestage glaucoma through medication, surgery, and combination therapies did not result in significant improvement (Pratista et al 2022). In Nigeria, the National Blindness and Visual Impairment Survey conducted in 2005-2007 reported that 4.2% of people aged >40 years were blind and 11.5% had moderate to severe visual impairment (Gascoyne et al 2022).…”
Section: Introductionmentioning
confidence: 99%